Evaluation of 5-year-old children with complete cleft lip and palate: Multicenter study. Part 1: Lip and nose aesthetic results. Issue 10 (December 2015) - Dissaux, Caroline; Bodin, Frédéric; Grollemund, Bruno; Picard, Arnaud; Vazquez, Marie-Paule; Morand, Béatrice; James, Isabelle; Kauffmann, Isabelle; Bruant-Rodier, Catherine
Abstract: Background and purpose: Cleft surgery is marked by all the controversies and the multiplication of protocols, as it has been shown by the Eurocleft study. The objective of this pilot study is to start a comparison and analyzing procedure between primary surgical protocols in French centers. Methods: Four French centers with different primary surgical protocols for cleft lip and palate repair, have accepted to be involved in this retrospective study. In each center, 20 consecutive patients with complete cleft lip and palate (10 UCLP and 10 BCLP per center), non syndromic, have been evaluated at a mean age of 5 [4, 6]. In this first part, the aesthetic results of nose and lip repair were assessed based on the scale established by Mortier et al. (1997). Results: Considering nose outcome, primary cleft repair surgery including a nasal dissection gives a statistically significant benefit in terms of septum deviation. Considering lip result, muscular dehiscence rate is significantly higher in BCLP patients with a two-stage lip closure. The centers using Millard one-stage lip closure do not have uniform results. For UCLP patients, the quality of scar is not statistically different between Skoog and Millard techniques. Conclusions: Primary results based on a simple, reproducible evaluation protocol. Extension to other centers required. Level of evidence: : Therapeutic study. Level III/retrospective multicenter comparative study.